Comparison and analysis of two measurement systems of horizontal atmospheric extinction of solar radiation. (15th September 2021) - Barbero, F.J.; López, G.; Ballestrín, J.; Bosch, J.L.; Alonso-Montesinos, J.; Carra, M.E.; Marzo, A.; Polo, J.; Fernández-Reche, J.; Batlles, F.J.; Enrique, R.
Abstract: Direct normal irradiance is the component of solar radiation exploited by concentrating solar power plants. However, solar radiation reflected by heliostats can be partially extinguished on its way to the receivers in solar power tower plants. These energy losses are accentuated with the distance travelled by the light. The growing development of solar power tower plants has highlighted the interest in determining this phenomenon. This paper presents the results of a six-month intercomparison campaign of the two most promising extinction measuring systems. The system developed at Plataforma Solar de Almería (SE Spain) is based on a direct measurement methodology by using two digital cameras. The second system indirectly estimates the extinction from forward-scatter meter (FSM) measurements. Two FSMs were used in this study. Both FSMs provided the same Meteorological Optical Range (MOR) trends, with differences into declared error margins. A selected number of days corresponding to medium to high aerosol loads have been used to assess the performance of both types of systems. Results show that, in these days, the atmospheric extinction coefficient values derived from the two-camera system were on average 2.1 times higher than those determined with the FSMs. Semi-empirical and empirical corrections for the aerosol spectral characteristics and for the content of water vapour in the atmosphere have been applied to the FSM measurements so that both systems provide similar values of horizontal attenuation. Highlights: Solar radiation horizontal attenuation values from two different systems during a 6-month campaign have been compared. One system is based on two identical digital cameras and other on forward-scatter meters (FSM). Discrepancies between both systems have been found that largely depend on the type of aerosol. An algorithm has been described to correct the FSM measurements for aerosols and water vapour on the surface.